2008
DOI: 10.1109/led.2008.918420
|View full text |Cite
|
Sign up to set email alerts
|

Superior n-MOSFET Performance by Optimal Stress Design

Abstract: The high-performance n-FET is achieved by ultrahigh-stress contact-etch-stop-layer stressor and optimal design of device dimensions. The biaxial-like stress resulting from a high symmetry in device dimension (gate width/gate length ratio is close to one) has the better performance in terms of I on enhancement, ballistic efficiency, and injection velocity. The multichannel device with a smaller gate width/gate length ratio is proposed to enhance the device performance in the circuit design for the n-FET. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It indicates that the reduction W can effectively enhance carrier mobility. It could be attributed the increase of tensile stress along channel width direction [8]. Furthermore, it is also found that the strain effects of SMT and strain contact etch stop layer (CESL) are similar as W scaled down.…”
Section: Resultsmentioning
confidence: 90%
“…It indicates that the reduction W can effectively enhance carrier mobility. It could be attributed the increase of tensile stress along channel width direction [8]. Furthermore, it is also found that the strain effects of SMT and strain contact etch stop layer (CESL) are similar as W scaled down.…”
Section: Resultsmentioning
confidence: 90%
“…All simulated drive current differences in this work are due to the stress. Stress impact on device mobility is captured using a model of related strained Si theory [12,13].…”
Section: Methodsmentioning
confidence: 99%
“…All simulated drive current differences in this work are due to the stress. Stress impact on the device mobility is captured with the model of related strained Si theory [12][13].…”
Section: IImentioning
confidence: 99%